Physic Nut Thrips Diversity - Asbani, Nur; Sartiami, Dewi (AGRIVITA Journal of Agricultural Science, 2011)
Physic nut (Jatropha curcas L.) is a relatively new agricultural crop commodity in Indonesia. Hence, the thrips associated with this plant are not well recognized. The research objective was to provide information and tool for identification of thrips associated with physic nut. Survey method was conducted in some areas of Java, Madura, and Lombok island. The results showed that 10 species of thrips were found associated with physic nut. They belonged to nine genera and three family i.e. Thripidae, Aeolothripidae and Phlaeothripidae and one unidentified species. The Thripidae species were Selenothrips rubrocintus, Rhipiphorothrips pulchellus, Thrips hawaiiensis, Heliothrips haemorrhoidalis, Zaniothrips ricini and Scolothrips sexmaculatus. The family Aeolothripidae were Franklinothrips vespiformis, F. variegatus and Mymarothrips bicolor; the only one of Phlaeothripidae was Ecacanthothripstibialis. The identification key had been built for all species mentioned above. These thrips can be grouped into herbivore, carnivore, and fungivore.Keywords: Jatropha curcas, thrips, diversity